The Contribution of Tourism Sector to Locally Generated Revenue in Indonesia’s Top Priority Tourist Destination - Najwa Khairina; Leni Anggraeni (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
This research is aimed to analyze the association between tourist expenditure, labor force in accommodation sector and room occupancy rate with locally generated revenue (PAD) in five province of top priority tourist destination in Indonesia (North Sumatera, Central Java, West and East Nusa Tenggara and North Sulawesi). We use data of tourism statistics from Statistics Bureau and Ministry of Creative Economy. By applying random effect panel data analysis, we found that all variables are significantly associated with PAD. Our empirical estimates shows that a one percent increase of labor force in accommodation sector is associated with 0.0075% increase in PAD, one percent increase of room occupancy rate associated with 2.85% increase in PAD while one percent increase of tourist expenditure is associated with 0.257% increase in PAD. The individual effect estimates show higher impact in Central Java and North Sumatera compared to West and East Nusa Tenggara and North Sulawesi and thus further confirming our presumption that there are some disparities between tourism spots in West and Eastern part of Indonesia.